Super-hydrophilic-underwater super-oleophobic graphene sponge for oil-water separation and preparation method of super-hydrophilic-underwater super-oleophobic graphene sponge
Graphene oxide was prepared by the improved Hummers method, and combined with chitosan and polyurethane sponge, super hydrophilic-underwater superoleophobic graphene sponge was prepared, which solved the problems of low efficiency and high cost of existing oil-water separation technology, and achieved efficient, low-cost and environmentally friendly oil-water separation effects.
Patent Information
- Application Number
- CN202510135989.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing oil-water separation technology has problems such as low efficiency, high cost, and environmental pollution. Especially in the treatment of water-rich and oil-containing wastewater, it is difficult for traditional methods to separate efficiently.
Graphene oxide (GO) was prepared by the improved Hummers method, combining chitosan (CS) and polyurethane sponge (PU), and super hydrophilic-underwater super oleophobic graphene sponge (GO@CS-PU) was prepared by a two-step impregnation method. The material had a water contact angle of 0° in the air and a contact angle of underwater oil reached 150.06°, and had the properties of super hydrophilic-underwater super oleophobic.
It has achieved efficient separation of various oil and water mixtures under gravity, with a separation efficiency of more than 95%, and the separation efficiency has not been significantly reduced after 10 uses, and has good reusability and wear resistance.
Smart Images

Figure CN119793400A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials and oil-water separation, and in particular to a super-hydrophilic-underwater super-oleophobic graphene sponge for oil-water separation and a preparation method thereof. Background Art
[0002] Water resources are closely related to human daily life and industrial development, and water shortages restrict the sustainable development of countries and regions. However, with the rapid expansion of fossil energy extraction, the oil industry is facing severe oil-water separation problems. In the process of oil extraction, storage, transportation and refining, a large amount of oil-water mixture will inevitably be produced, which brings challenges to the development of oily wastewater treatment technology and equipment. In addition, oil spills caused by offshore crude oil extraction and transportation not only lead to resource waste and economic losses, but also threaten human health and the ecological environment. The shortcomings of traditional oil-water separation technology are gradually emerging. Gravity separation, filtration, centrifugal separation and flotation have the disadvantages of low efficiency, poor stability, high operating cost and high total cost, respectively. Therefore, efficient, green and low-cost oil-water separation methods are urgently needed. In recent years, various functional materials with special wettability have been developed to separate oil and water, which can be divided into two categories: superhydrophobic superoleophilic materials and superhydrophilic underwater superoleophobic materials. The former allows oil to pass through or be absorbed, while the latter allows water to pass through.
[0003] Although the use of superoleophilic and hydrophobic materials for oil-water separation has the advantages of easy preparation of materials and good oil-water separation effect, there are still some defects in practical applications. For example, in long-term operation, the oleophilic pores are easily contaminated by residual oil, resulting in oil penetration and reduced separation efficiency. In addition, the density of oil is usually lower than that of water, and the water layer is in the lower layer due to gravity, which can prevent oil penetration during gravity-driven separation. Therefore, such materials are not suitable for treating water-rich oily wastewater. Superhydrophilic and superoleophobic materials are more conducive to oil-water separation. From the perspective of practical operation, the development of hydrophilic and oleophobic materials provides another feasible way for oil-water separation. However, according to the Young equation and Fowkes theory, it is difficult to prepare hydrophilic and oleophobic surfaces simultaneously in air. In most cases, oleophobic surfaces are also hydrophobic because the surface tension of water is higher than that of oil and organic solvents, so current research has turned to the construction of underwater oleophobic surfaces.
[0004] It is well known that graphene oxide (GO) contains many oxygen-containing functional groups (OFGs), such as hydroxyl, carboxyl, carbonyl, and epoxy groups, which make GO hydrophilic. GO-modified metal meshes and membranes are common hydrophilic-underwater oleophobic oil-water separation materials. The hydration layer helps oil-water separation, and the oleophobicity prevents the metal meshes and membranes from being contaminated by oil. However, most underwater oleophobic surfaces of GO-modified metal meshes and membranes are made through cumbersome modification processes, which limits their scalability and potential for further application. Moreover, metal meshes and membranes are further limited in the application scenarios of oil-water separation because they mostly play a single filtering role and cannot have more oil-water separation application scenarios like hydrophilic-underwater oleophobic porous materials. Therefore, it is of great significance to develop functional materials with hydrophilicity and underwater oleophobicity in a cost-effective and multifunctional application scenario. Summary of the invention
[0005] The purpose of the present invention is to obtain an efficient, green and low-cost oil-water separation material and method, and to provide a super-hydrophilic-underwater super-oleophobic graphene sponge for oil-water separation and a preparation method thereof.
[0006] In a first aspect, the present invention provides a method for preparing a super-hydrophilic-underwater super-oleophobic graphene sponge for oil-water separation, comprising:
[0007] Step 1, weigh 4g of flake graphite, 2g of sodium nitrate, and 92mL of concentrated sulfuric acid in a beaker, place the beaker in an ice-water mixture environment and magnetically stir for 0.5h, then add 4g of potassium permanganate to the beaker every 15min, for a total of three times, and continue to react for 1h after the addition is completed, and the low-temperature reaction stage ends;
[0008] After the low temperature reaction stage, the beaker was transferred to a 35°C constant temperature water bath and stirred for 2 hours before the medium temperature reaction stage ended;
[0009] After the medium-temperature reaction stage, the temperature of the constant-temperature water bath was changed to 95°C, magnetic stirring was continued, and 200 mL of deionized water was added dropwise. After the temperature of the reaction system rose to 95°C, 400 mL of deionized water and 100 mL of hydrogen peroxide were added after 5 minutes to obtain a dispersion with a bright yellow metallic luster. After the reaction was continued for 15 minutes, the high-temperature reaction stage was terminated.
[0010] Step 2: After the high temperature reaction stage, the beaker is removed from the water bath, the obtained dispersion is ultrasonically dispersed for 30 minutes, hydrochloric acid is added and stirred for 3 minutes, and finally the obtained GO dispersion is diluted to 10L with deionized water, and the upper clear liquid is poured off by natural gravity precipitation. After repeating this step three times, the pH of the GO dispersion is neutral; the lower layer of GO slurry after the third precipitation is freeze-dried to obtain solid GO, which is shredded into fine powder and placed in a dryer for standby use;
[0011] Step three, cut the polyurethane sponge into a cubic shape, ultrasonically clean it with ethanol and pure water for 3 times, and then dry it for use; prepare a GO dispersion with a concentration of 2.5-5 mg / mL, weigh GO and add it to a beaker filled with deionized water for ultrasonic dispersion for 0.5h; immerse the original PU in the GO dispersion, repeatedly squeeze and dip it 5 times, then take it out after ultrasonic dispersion for 1h, and dry it in an electric constant temperature blast drying oven with a drying temperature of 55°C to obtain GO-PU; prepare a CS aqueous solution with a mass concentration of 0.15%-0.6%, weigh CS and dissolve it in an acetic acid solution with a solid content of 2%, and magnetically stir it at room temperature for 4h; immerse the prepared GO-PU in the CS aqueous solution, slowly squeeze and dip it 3 times, then take it out, and dry it in an electric constant temperature blast drying oven with a drying temperature of 55°C to obtain GO@CS-PU.
[0012] Furthermore, in step three, the concentration of the GO dispersion is 3-4.5 mg / mL.
[0013] Furthermore, in step three, the mass concentration of CS is 0.2%-0.5%.
[0014] In a second aspect, the present invention provides a super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation prepared by the preparation method of the super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation described above.
[0015] The present invention has the following beneficial effects: a super-hydrophilic-underwater super-oleophobic graphene sponge for oil-water separation of the present invention and a preparation method thereof, graphene oxide is prepared by an improved Hummers method, GO and chitosan are used as modified raw materials, polyurethane sponge is used as a matrix, and a super-hydrophilic-underwater super-oleophobic sponge is prepared by a two-step impregnation method. The addition of GO can increase the roughness and hydrophilicity of the sponge surface, the addition of CS can increase the hydrophilicity of the sponge and the stability of the GO coating, and the combination of the two acts together to make the water contact angle in the air of the modified sponge reach 0 °, and the contact angle of chloroform underwater is 150.06 °, which has the performance of super-hydrophilic-underwater super-oleophobic. Modified PU has good elastic properties, good thermal stability and water absorption capacity. The oil-water separation performance test shows that a variety of oil-water mixtures can be separated by gravity alone, and the separation efficiency of various oil-water mixtures can reach more than 95%; the good reusability of the modified PU means that its separation efficiency has not been significantly reduced after 10 uses; when the pump provides dynamic external force, static continuous oil-water separation in a non-stirring state and dynamic continuous oil-water separation in a stirring state can be achieved; after 10 wear cycles, the modified PU can still maintain a high oil-water separation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1The XRD spectra and Raman spectra of graphite, GO and rGO in Example 1; (a) is the XRD spectra of graphite and GO; (b) is the Raman spectra of graphite and GO;
[0017] Figure 2 SEM characterization images of original PU, GO-PU and GO@CS-PU in Example 1; (a) and (b) are original PU; (c) and (d) are GO-PU; (e) and (f) are GO@CS-PU;
[0018] Figure 3 The infrared spectra of graphite, GO, CS, original PU, GO-PU and GO@CS-PU in Example 1; (a) is the infrared spectra of graphite, GO and CS; (b) is the infrared spectra of original PU, GO-PU and GO@CS-PU;
[0019] Figure 4 The TGA graphs of graphite, GO, CS, original PU, GO-PU and GO@CS-PU in Example 1; (a) is the TGA graph of graphite, CS and GO; (b) is the TGA graph of PU, GO-PU and GO@CS-PU;
[0020] Figure 5 The separation efficiency diagram of GO@CS-PU obtained in Example 1 for olive oil / water, lubricating oil / water, rapeseed oil / water, diesel / water, toluene / water and n-hexane / water mixtures, and the separation efficiency comparison diagram of GO@CS-PU for olive oil / water, diesel / water, and n-hexane / water mixtures with the number of separation cycles; (a) is the separation efficiency diagram of GO@CS-PU for olive oil / water, lubricating oil / water, rapeseed oil / water, diesel / water, toluene / water and n-hexane / water mixtures; (b) is the separation efficiency comparison diagram of GO@CS-PU for olive oil / water, diesel / water, and n-hexane / water mixtures with the number of separation cycles;
[0021] Figure 6 This is a diagram showing the effect of GO@CS-PU obtained in Example 4 on the separation performance of diesel / water mixture under different wear cycles. DETAILED DESCRIPTION
[0022] The following non-limiting embodiments can enable ordinary technicians in the field to understand the present invention more comprehensively, but do not limit the present invention in any way. It is necessary to point out that the following embodiments cannot be understood as limiting the scope of protection of the present invention. If technical personnel skilled in the art make some non-essential improvements and adjustments to the present invention based on the above-mentioned content of the present invention, they still fall within the scope of protection of the present invention.
[0023] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with the embodiments. It should be noted that the following detailed descriptions are all illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those generally understood by those of ordinary skill in the art to which the present application belongs.
[0024] The present invention adopts a simple, efficient and environmentally friendly method for oil-water separation, that is, graphene oxide (GO) is prepared by an improved Hummers method, GO and chitosan (CS) are used as modified raw materials, polyurethane sponge (PU) is used as a matrix, and a super hydrophilic-underwater super oleophobic sponge (GO@CS-PU) is prepared by a two-step impregnation method. The addition of GO can increase the roughness and hydrophilicity of the sponge surface, and the addition of CS can increase the hydrophilicity of the sponge and the stability of the GO coating. The combination of the two acts together to make the water contact angle of the modified sponge in the air reach 0°, and the contact angle of chloroform underwater is 150.06°, which has the performance of super hydrophilic-underwater super oleophobic. The modified PU has good elastic properties, good thermal stability and water absorption capacity. The oil-water separation performance test shows that a variety of oil-water mixtures can be separated by gravity alone, and the separation efficiency of various oil-water mixtures can reach more than 95%; the good reusability of the modified PU means that its separation efficiency has not been significantly reduced after 10 uses; when the pump provides dynamic external force, static continuous oil-water separation in a non-stirring state and dynamic continuous oil-water separation in a stirring state can be achieved; after 10 wear cycles, the modified PU can still maintain a high oil-water separation performance.
[0025] The present invention also relates to a method for preparing the super-hydrophilic-underwater super-oleophobic graphene sponge, comprising the following steps:
[0026] 1. Graphene oxide (GO) was prepared using the improved Hummers method. The specific steps are as follows.
[0027] 1) Low temperature stage
[0028] Weigh 4 g of flake graphite, 2 g of sodium nitrate, and 92 mL of concentrated sulfuric acid into a beaker, place the beaker in an ice-water mixture and magnetically stir for 0.5 h, then quantitatively add 4 g of potassium permanganate into the beaker every 15 min for a total of three times. After the addition is completed, continue the reaction for 1 h before the low-temperature reaction stage ends.
[0029] 2) Medium temperature stage
[0030] After the low-temperature reaction stage, the beaker was transferred to a 35°C constant temperature water bath and stirred for 2 h before the medium-temperature reaction stage ended.
[0031] 3) High temperature stage
[0032] After the reaction in the medium temperature stage is completed, the temperature of the constant temperature water bath is changed to 95°C, magnetic stirring is continued, and 200 mL of deionized water is slowly added drop by drop. After the temperature of the reaction system rises to 95°C, wait for another 5 minutes and then slowly add 400 mL of deionized water and 100 mL of hydrogen peroxide. At this time, a dispersion with a bright yellow metallic luster is obtained. After continuing the reaction for 15 minutes, the high temperature reaction stage is completed.
[0033] 2. Washing
[0034] After the high temperature reaction stage, the beaker was removed from the water bath, the obtained dispersion was ultrasonically dispersed for 30 minutes, hydrochloric acid was added and stirred for 3 minutes, and finally the obtained GO dispersion was diluted to 10L with deionized water, and the upper clear liquid was poured off by natural gravity precipitation. After repeating this step three times, the pH of the GO dispersion was neutral. The lower GO slurry after the third precipitation was freeze-dried to obtain solid GO, which was shredded into fine powder and placed in a dryer for later use.
[0035] 3. Super hydrophilic - underwater super oleophobic graphene sponge method
[0036] The commercial polyurethane sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and then dried for use. A GO dispersion with a concentration of 2.5-5 mg / mL was prepared, and further, the concentration of the GO dispersion was optimized to 3-4.5 mg / mL. A certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5h. Then the original PU was immersed in the GO dispersion, repeatedly squeezed and dipped 5 times, and then ultrasonically dispersed for 1h, and then taken out, and dried in an electric constant temperature blast drying oven at a drying temperature of 55°C to obtain GO-PU. A CS (chitosan) aqueous solution with a mass concentration of 0.15%-0.6% was prepared, and further, the mass concentration of CS was optimized to 0.2%-0.5%. A certain mass of CS was weighed and dissolved in an acetic acid solution with a solid content of 2%, and magnetically stirred at room temperature for 4h. The prepared GO-PU was immersed in a CS aqueous solution, slowly squeezed and dipped for 3 times, then taken out, and dried in an electric constant temperature blast drying oven at a drying temperature of 55°C to obtain GO@CS-PU.
[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with Examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or the conditions recommended by the manufacturer, and the reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0038] Embodiment 1:
[0039] GO was prepared by the improved Hummers method. The commercial polyurethane sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and dried for use. A GO dispersion with a concentration of 3 mg / mL was prepared, and a certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5 h. Then the original PU was immersed in the GO dispersion, repeatedly squeezed and dipped 5 times, and then ultrasonically taken out for 1 h, and dried in an electric constant temperature blast drying oven at a drying temperature of 55 ° C to obtain GO-PU. A CS aqueous solution with a mass concentration of 0.2% was prepared, and a certain mass of CS was weighed and dissolved in an acetic acid solution with a solid content of 2%, and magnetically stirred at room temperature for 4 h. The prepared GO-PU was immersed in the CS aqueous solution, slowly squeezed and dipped 3 times, and then taken out, and dried in an electric constant temperature blast drying oven at a drying temperature of 55 ° C to obtain GO@CS-PU.
[0040] See also Figure 1-Figure 5 :(1) The water contact angle of GO@CS-PU in air is 0°, and the maximum oil contact angle can reach 150.06° underwater. (2) The prepared GO was characterized by XRD, Raman spectroscopy, FTIR and TGA. The results showed that GO was successfully prepared by flake graphite. CS was characterized by FTIR and TGA, and GO@CS-PU was characterized by SEM, FTIR and TGA. The results showed that GO and CS were successfully loaded on PU, and GO@CS-PU can be used normally at an ambient temperature of about 150°C. (3) The adsorption (water)-extrusion cycle test showed that after 20 cycles of cyclic adsorption-extrusion, the sponge was 18.9753g / g, and it still maintained a good water absorption capacity. The contact angle of chloroform underwater can still reach 147.64°. The CS modification agent can not only enhance the hydrophilicity of PU but also enhance the adhesion of the GO coating on the sponge surface, reducing the shedding situation. (4) The oil-water separation performance test shows that the separation efficiency of GO@CS-PU for olive oil / water, motor oil / water, rapeseed oil / water, diesel / water, toluene / water and n-hexane / water mixtures is as high as 95.2%, 95.7%, 96.5%, 97.6%, 99.2% and 99.4%, respectively. GO@CS-PU shows excellent reusability. Even after 10 cycles of separation, the separation efficiency of olive oil / water, diesel / water, and n-hexane / water mixtures is 98.3%, 96.8% and 94.3%, respectively. The material still has a good oil-water separation effect.
[0041] Embodiment 2:
[0042] GO was prepared by the improved Hummers method. The commercial polyurethane sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and dried for use. A GO dispersion with a concentration of 3.5 mg / mL was prepared, and a certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5 h. Then the original PU was immersed in the GO dispersion, repeatedly squeezed and dipped 5 times, and then ultrasonically taken out for 1 h, and dried in an electric constant temperature blast drying oven at a drying temperature of 55 ° C to obtain GO-PU. A CS aqueous solution with a mass concentration of 0.3% was prepared, and a certain mass of CS was weighed and dissolved in an acetic acid solution with a solid content of 2%, and magnetically stirred at room temperature for 4 h. The prepared GO-PU was immersed in the CS aqueous solution, slowly squeezed and dipped 3 times, and then taken out, and dried in an electric constant temperature blast drying oven at a drying temperature of 55 ° C to obtain GO@CS-PU.
[0043] GO@CS-PU can continuously separate oil and water when used under the external force provided by a pump, with separation efficiencies of 98.4% and 99.1% for diesel / water and tetrachloroethylene / water mixtures.
[0044] Embodiment 3:
[0045] GO was prepared by the improved Hummers method. The commercial polyurethane sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and dried for use. A GO dispersion with a concentration of 4 mg / mL was prepared, and a certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5 h. Then the original PU was immersed in the GO dispersion, repeatedly squeezed and dipped 5 times, and then ultrasonically taken out for 1 h, and dried in an electric constant temperature blast drying oven at a drying temperature of 55 ° C to obtain GO-PU. A CS aqueous solution with a mass concentration of 0.4% was prepared, and a certain mass of CS was weighed and dissolved in an acetic acid solution with a solid content of 2%, and magnetically stirred at room temperature for 4 h. The prepared GO-PU was immersed in the CS aqueous solution, slowly squeezed and dipped 3 times, and then taken out, and dried in an electric constant temperature blast drying oven at a drying temperature of 55 ° C to obtain GO@CS-PU.
[0046] Under the dynamic condition of severe stirring of the oil-water mixture, GO@CS-PU can still maintain good continuous oil-water separation performance.
[0047] Embodiment 4:
[0048] GO was prepared by the improved Hummers method. The commercial polyurethane sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and dried for use. A GO dispersion with a concentration of 4.5 mg / mL was prepared, and a certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5 h. Then the original PU was immersed in the GO dispersion, repeatedly squeezed and dipped 5 times, and then ultrasonically taken out for 1 h, and dried in an electric constant temperature blast drying oven at a drying temperature of 55 ° C to obtain GO-PU. A CS aqueous solution with a mass concentration of 0.4% was prepared, and a certain mass of CS was weighed and dissolved in an acetic acid solution with a solid content of 2%, and magnetically stirred at room temperature for 4 h. The prepared GO-PU was immersed in the CS aqueous solution, slowly squeezed and dipped 3 times, and then taken out, and dried in an electric constant temperature blast drying oven at a drying temperature of 55 ° C to obtain GO@CS-PU.
[0049] from Figure 6 It can be seen that after ten wear cycles, the separation efficiency of GO@CS-PU for diesel / water mixture changed from 97.6% before wear to 96.2% after wear, and the separation time changed from 2 min to 98 s, still maintaining a high separation efficiency.
[0050] The characterization of the prepared GO and the structural characterization and performance testing methods of the modified sponge samples in this application include:
[0051] (1) Infrared analysis: The KBr pelleting method was used to grind the dried sample powder and then press it into pellets. The mass ratio of sample to KBr was 1 / 100, and the sample was analyzed by FTIR.
[0052] (2) Thermal stability analysis: The samples were subjected to thermogravimetric analysis using TG in a nitrogen atmosphere with a heating rate of 10 °C / min and a temperature range of 40 to 600 °C.
[0053] (3) Morphology observation: SEM was used to observe the morphology of the sample surface at different magnifications;
[0054] (4) Characterization of surface wettability: The wettability of the sponge surface was characterized using a contact angle meter. A certain volume of pure water droplets and oil (organic solvent) droplets were dripped into the needle, and the static contact angle of the sample surface was tested at room temperature.
[0055] (5) Adsorption (water)-extrusion cycle test: In order to test the adsorption (water) performance and recycling performance of the prepared samples, the dried modified PU was cut into blocks (2 cm × 2 cm × 1 cm), accurately weighed and immersed in deionized water. After fully adsorbing for 2 min, it was taken out to make it saturated with water. The sponge was taken out with dry and clean tweezers. After the water droplets stopped dripping, its weight after absorbing water was weighed, and the water absorption multiple of the modified PU (Qw, the maximum water absorption mass corresponding to the unit mass of sponge, g / g) was calculated using formula (1). The modified PU after saturated water absorption was weighed, and then the sponge was repeatedly squeezed with tweezers until no more water drops overflowed. After weighing, the saturated water absorption experiment was continued, and the squeezed water was collected in a dry beaker. The above squeezing-adsorption experiment was repeated 20 times, and the saturated mass water absorption capacity of the sponge under different recycling times was calculated according to formula (1).
[0056] Q w =(m1-m0) / m0(1)
[0057] Where: m1—mass of the sponge after saturation with water, g
[0058] m0—mass of the sponge before absorbing water, g
[0059] (6) Oil-water separation performance test: The original dry PU and modified PU were cut into circles with a radius of 4 cm and sandwiched between two glass tubes; the modified PU was pre-wetted with deionized water, and then a mixture of diesel, toluene, n-hexane, rapeseed oil, olive oil or motor oil (25 mL) and deionized water (100 mL) was added to the system as a test solution to conduct an oil (organic solvent)-water separation experiment; the oil or organic solvent was dyed with Sudan III to obtain visual clarity; the separation time when the oil or organic solvent stopped dripping through the sponge was recorded; the entire separation process was completely driven by gravity without external force; the oil-water separation efficiency (R0, %) was calculated according to formula (2); the above steps were repeated 20 times for diesel, olive oil and n-hexane, and the oil-water separation efficiency (R0, %) was calculated according to formula (2)
[0060] Calculate its oil-water separation efficiency;
[0061] R0=m3 / m2×100%(2)
[0062] Where: m2—initial oil mass, g
[0063] m3—mass of oil collected on the upper layer of the glass funnel, g
[0064] (7) Continuous oil-water separation performance test: The continuous removal of water from the oil-water mixture using the modified PU is carried out through a pump-assisted process; the oil-water mixture is selectively separated under continuous dynamic conditions by a self-assembled separation device, that is, a hose with a needle at one end is inserted into the pre-wetted modified PU, which is immersed in a conical flask containing a mixture of diesel or tetrachloroethylene (25 mL, dyed with Sudan III) and deionized water (100 mL); the other end of the hose with a needle is placed in a conical flask to collect water; the hose is connected to a peristaltic pump, and under the external power provided by the pump, water begins to be sucked out through the modified PU, and the speed of oil-water separation can be adjusted with the speed of the peristaltic pump. The oil-water separation efficiency can be calculated as the volume ratio of the diesel remaining in the conical flask after the oil-water separation to the diesel added to the oil-water mixture before separation. In addition, a stirrer is added to the oil-water mixture to simulate the dynamic flow conditions of oily wastewater in the actual environment, and a dynamic continuous oil-water separation experiment is carried out.
[0065] (8) Mechanical stability-wear test: The modified PU was cut into circular samples with a radius of 4 cm, placed on sandpaper under a 200 g weight and moved 50 mm, which represented one wear cycle. Every 5 times was counted as one cycle. The diesel / water separation performance was measured once after each cycle of wear. The worn side of the sample was used for diesel / water mixture separation using the same method as the oil-water separation performance test to evaluate its wear resistance.
[0066] From the above examples, it can be seen that the present invention uses the improved Hummers method to prepare graphene oxide, uses a simple and mild two-stage impregnation method to load GO and CS on PU in sequence, and performs joint hydrophilic modification on PU to successfully prepare super-hydrophilic GO@CS-PU. The water contact angle of the modified PU in air is 0°, and the oil contact angle under water can reach 151.60°.
[0067] The prepared GO was characterized by XRD, Raman spectroscopy, FTIR and TGA, and the results showed that GO was successfully prepared by flake graphite. CS was characterized by FTIR and TGA, and GO@CS-PU was characterized by SEM, FTIR and TGA, and the results showed that GO and CS were successfully loaded on PU, and GO@CS-PU could be used normally at an ambient temperature of about 150°C.
[0068] The adsorption (water)-extrusion cycle test showed that after 20 cycles of adsorption-extrusion, the sponge weight was 18.9753 g / g, still maintaining a good water absorption capacity, and the contact angle of underwater chloroform could still reach 147.64°. The CS modification reagent can not only enhance the hydrophilicity of PU but also enhance the adhesion of GO coating on the sponge surface and reduce shedding.
[0069] The oil-water separation performance test shows that the separation efficiency of GO@CS-PU for olive oil / water, engine oil / water, rapeseed oil / water, diesel / water, toluene / water and n-hexane / water mixtures is as high as 95.2%, 95.7%, 96.5%, 97.6%, 99.2% and 99.4%, respectively. GO@CS-PU shows excellent reusability. Even after 10 cycles of separation, the separation efficiency of olive oil / water, diesel / water and n-hexane / water mixtures is 98.3%, 96.8% and 94.3%, respectively. The material still has a good oil-water separation effect. GO@CS-PU can continue to separate oil and water continuously when used under the external force provided by the pump. The separation efficiency of diesel / water and tetrachloroethylene / water mixtures is 98.4% and 99.1%. Even under poor dynamic oil-water mixture conditions, GO@CS-PU can still maintain good continuous oil-water separation performance.
[0070] Mechanical stability tests show that after ten wear cycles, the separation efficiency of GO@CS-PU for diesel / water mixture changed from 97.6% before wear to 96.2% after wear, and the separation time changed from 2 minutes to 98 seconds, still maintaining a high separation efficiency.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation, characterized in that: include: Step 1, weigh 4g of flake graphite, 2g of sodium nitrate, and 92mL of concentrated sulfuric acid in a beaker, place the beaker in an ice-water mixture environment and magnetically stir for 0.5h, then add 4g of potassium permanganate to the beaker every 15min, for a total of three times, and continue to react for 1h after the addition is completed, and the low-temperature reaction stage ends; After the low temperature reaction stage, the beaker was transferred to a 35°C constant temperature water bath and stirred for 2 hours before the medium temperature reaction stage ended; After the medium-temperature reaction stage, the temperature of the constant-temperature water bath was changed to 95°C, magnetic stirring was continued, and 200 mL of deionized water was added dropwise. After the temperature of the reaction system rose to 95°C, 400 mL of deionized water and 100 mL of hydrogen peroxide were added after 5 minutes to obtain a dispersion with a bright yellow metallic luster. After the reaction was continued for 15 minutes, the high-temperature reaction stage was terminated. Step 2: After the high temperature reaction stage, the beaker is removed from the water bath, the obtained dispersion is ultrasonically dispersed for 30 minutes, hydrochloric acid is added and stirred for 3 minutes, and finally the obtained GO dispersion is diluted to 10L with deionized water, and the upper clear liquid is poured off by natural gravity precipitation. After repeating this step three times, the pH of the GO dispersion is neutral; the lower layer of GO slurry after the third precipitation is freeze-dried to obtain solid GO, which is shredded into fine powder and placed in a dryer for standby use; Step three, cut the polyurethane sponge into a cubic shape, ultrasonically clean it with ethanol and pure water for 3 times, and then dry it for use; prepare a GO dispersion with a concentration of 2.5-5 mg / mL, weigh GO and add it to a beaker filled with deionized water for ultrasonic dispersion for 0.5h; immerse the original PU in the GO dispersion, repeatedly squeeze and dip it for 5 times, then take it out after ultrasonic dispersion for 1h, and dry it in an electric constant temperature blast drying oven with a drying temperature of 55°C to obtain GO-PU; prepare a CS aqueous solution with a mass concentration of 0.15%-0.6%, weigh CS and dissolve it in an acetic acid solution with a solid content of 2%, and magnetically stir it at room temperature for 4h; immerse the prepared GO-PU in the CS aqueous solution, slowly squeeze and dip it for 3 times, then take it out, and dry it in an electric constant temperature blast drying oven with a drying temperature of 55°C to obtain GO@CS-PU.
2. A method for preparing a super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation as claimed in claim 1, characterized in that, In step 3, the concentration of GO dispersion is 3-4.5 mg / mL.
3. A method for preparing a super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation as claimed in claim 1, characterized in that, In step 3, the mass concentration of CS is 0.2%-0.5%.
4. A super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation obtained by the preparation method of the super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation as described in any one of claims 1 to 3.